Method of mathematical modeling in the meliorative geography and recreation - Rezunenko, V. O.; Kobchenko, Yu. F.; Kobchenko, O. Yu. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
The actuality of the problem is determined by dependence of agriculture on the natural factors, and in particular, on the weather-climate conditions. All components of natural-agromeliorative systems and in particular hydrometeorological factors take an active part in the formation of agricultural crops. When solving these questions, it is necessary to have an objective estimation of the influence of the different factors including weather and climate on the level of agricultural production. This will allow us to determine contribution of various indicators of agro-meteorological conditions in the estimation of cereal harvest more reasonably. In this connection, the research of the weather-climatic conditions influence on the vegetation of agricultural crops in general and in the conditions of grain farming development in Kharkiv region, in particular.The method of mathematical modeling was chosen to study the problems formulated in the work. The study of the phenomena of nature and human activity without the use of mathematical methods is considered one-sided, because it does not take into account one of the important aspects of any study - the side of quantitative relationships and appropriateness. The result of the research is an analysis of statistical indicators of agricultural crops harvest and hydrometeorological conditions in Kharkiv region during the period 1972-2016.Having analyzed these indicators, we have determined that the quantitative dependence of the crop on the number of dry days is a complex nonlinear multi-parameter. At the same time, close connection between the harvest of corn and sugar beets with weather conditions was very significant, as indicated by the large correlation coefficient between them, which is equal to 0.87-0.90.We have worked out a hypothesis about the form of functional dependence between these components. Using method of mathematical modeling to analyze the spatio-temporal structure of natural-anthropogenic phenomenon development allows us to unify the hydrometeorological characteristics, and it can be used in different fields of science, in particular, in recreational geography.It is noted that recreational geography is the newest branch of knowledge, where mathematical methods occupy an important place in scientific research. The model of the natural-recreational system is proposed in the work. This allows us to introduce a complex study of interdisciplinary connections of investigated objects. The feature of the model is in the fact that it allows to cover all levels of the systems development from planning, designing and creating recreational systems, to estimation and forecast of their functioning.The scientific novelty of the study lies in the fact that the extended concept of the natural-recreational system is formulated, and the principles and methods of research, in particular, the method of mathematical modeling, allow us to consider the system as a holistic natural-anthropogy of formation. The methodical approach provides the interdisciplinary level of research of the natural-recreational system. It is possible to study the systemic nature of the system components connections.The practical value of the work focuses on the agricultural sector. The discovery of quantitative estimation of crops harvest dependence on weather factors allows us to calculate crop yields in each particular case. This technique can form the basis for forecasting crop yields.